Relevance of Compliance on Islamic Law by The Construction of MUI DSN Fatwa on MurÄbahah Financing Products at BMT Khasanah Tawang, Weru - May Shinta Retnowati; Inaiyaya Zuhrifa Allhumahira (e-Journal Ekonomi Bisnis dan Akuntansi, 2023)
MurÄbahah is one of the financing products at BMT Khasanah Tawang, Weru Sragen that is most in demand by customers or the public. Basically there are no ribawi provisions from the profits of murabahah transactions. The concept of murabaha contract transactions is more transparent, because murabaha schemes in financial institutions are required to notify customers about price objects or products and agree on the benefits received by the institution. So transactions must be carried out in a trustworthy and honest manner. In Murabahah there are conditions that must be met by financial institutions in Indonesia. According to DSN MUI Fatwa No. 04/DSN-MUI/IV/2000, the first provision of article no 5 that banks buy goods needed by customers on behalf of their own banks, and these purchases must be lawful and free of usury, in other words the bank must first purchase goods or assets ordered by customers legally and free from usury. And in the DSN-MUI fatwa number 17/DSN-MUI/IX/2000, it has been explained in the first decree no. 2 that customers who are unable or unable to pay due to force majeure may not be subject to sanctions. Problems at BMT Khasanah Weru are customers who use capital financing for personal needs. The method used in this research is descriptive qualitative, data collection is done by means of interviews, documentation and observation. The results of the research on the application of MurÄbahahat BMT Khasanah Tawang, Weru the application of Murabahah financing products is in accordance with DSN MUI fatwa No. 04/DSN-MUI/IV/2000 and DSN-MUI fatwa number 17/DSN-MUI/IX/2000. BMT Khasanah Tawang addresses the problems of customers who use capital financing to buy personal needs with several evaluations.